Comparison of allele frequency for HLA-DR and HLA-DQ between patients with ECC and caries-free children - Bagherian A; Nematollahi H; Afshari J; Moheghi N (Wolters Kluwer Medknow Publications, 2008)
Background: Early childhood caries (ECC) is one of the most common diseases of childhood. The etiology of ECC is multifactorial and both genetic and environmental factors play important roles in the pathogenesis of the disease. Genetic variations in the hosts may contribute to changes in the risk for dental caries. Genetic factors such as human leukocyte antigen (HLA) have recently been suggested as a predisposing factor. Aim: The aim of this study was to look for an association between HLA-DRB1 and HLA-DQB1 with ECC for developing new strategies for the diagnosis as well as the prevention of the disease. Design: In this study, we extracted the genomic DNAs from whole blood samples of 44 patients with ECC and 35 caries-free children by the salting-out method. We amplified the genomic DNA by PCR-SSP and then HLA-typing was performed for all alleles. Results: The results revealed a significant increase in the frequency of HLA-DRB1FNx0104 in the patient group (P = 0.019). The odds ratio for this allele was detected to be 10. The frequency of HLA-DQB1 alleles was not significantly different between the two groups. Conclusion: The above results suggest that HLA-DRB1FNx0104 is associated with the susceptibility to ECC. Thus HLA-DRB1FNx0104 detection as a molecular marker for early diagnosis of ECC may be recommended.